Central gender theoretical concepts in health research: the state of the art. Issue 2 (21st November 2013) - Hammarström, Anne; Johansson, Klara; Annandale, Ellen; Ahlgren, Christina; Aléx, Lena; Christianson, Monica; Elwér, Sofia; Eriksson, Carola; Fjellman-Wiklund, Anncristine; Gilenstam, Kajsa; Gustafsson, Per E; Harryson, Lisa; et al.
Abstract : Despite increasing awareness of the importance of gender perspectives in health science, there is conceptual confusion regarding the meaning and the use of central gender theoretical concepts. We argue that it is essential to clarify how central concepts are used within gender theory and how to apply them to health research. We identify six gender theoretical concepts as central and interlinked—but problematic and ambiguous in health science: sex, gender, intersectionality, embodiment, gender equity and gender equality. Our recommendations are that: the concepts sex and gender can benefit from a gender relational theoretical approach (ie, a focus on social processes and structures) but with additional attention to the interrelations between sex and gender; intersectionality should go beyond additive analyses to study complex intersections between the major factors which potentially influence health and ensure that gendered power relations and social context are included; we need to be aware of the various meanings given to embodiment, which achieve an integration of gender and health and attend to different levels of analyses to varying degrees; and appreciate that gender equality concerns absence of discrimination between women and men while gender equity focuses on women's and men's health needs, whether similar or different. We conclude that there is a constant need to justify and clarify our use of these concepts in order to advance gender theoretical development. Our analysis is an invitation for dialogue but also a call to make more effective use of the knowledge base which has already developed among gender theorists in health sciences in the manner proposed in this paper.